PENGUATAN PEMBELAJARAN MELALUI VALUE BASED EDUCATION - Asef Umar Fakhruddin (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2017)
The education purpose is to create the best generation, to educate good character, and also to build a vision. To get the target, the learning process should be touched by friendly hearted and minded, so the students could feel relax, comfortable and easy to understand. Value based education is one of the suitable method used in learning process in order to create optimal learning, give stimulant, and also to give spirit action. Value based education enrich the educators to understand and elaborate the subject and the course deeply, and then to convey to the students softly and communicational. Value based education invites the teachers to understand the core of material, subject, and than formulate it and also to convey softly and communicativelly to the students. It followed by guided and instruction. Through this way, all the student from the kindergarten to university student level can understand the core of its material. The goal is that they have knowledge to survive in the future. That is all about value based education. Key word: value based education, educator/teacher, student, subject.